The instruments of darkness : a novel [large type] - Connolly, John, 1968- (Connolly, John, 1968- Charlie Parker thriller, 2024)
"In Maine, Colleen Clark stands accused of the worst crime a mother can commit: the abduction and possible murder of her child. Everyone -- ambitious politicians in an election season, hardened police, ordinary folk -- has an opinion on the case, and most believe she is guilty. But most is not all. Defending Colleen is the lawyer Moxie Castin, and working alongside him is the private investigator Charlie Parker, who senses the tale has another twist, one involving a husband too eager to accept his wife's guilt, a group of fascists arming for war, a disgraced psychic seeking redemption, and an old, twisted house deep in the Maine woods, a house that should never have been built. A house, and what dwells beneath."--